Effect of macroeconomic, demographic and governance factors on income inequality of selected sub-Saharan Africa Countries - Bekele, Dagim Tadesse (Journal of Economic Development, Environment and People, 2019)
This research tried to look effect of macroeconomic, demographic and governance factors on income inequality in 34 sub-Saharan Africa countries by using unbalance panel data spanning from 2010 to 2017. Two step System GMM estimation was conducted for the econometrics analysis of Dynamic Panel Data model. The finding revealed income inequality has dynamic nature. Also Kuznets’ hypothesis is worked in these countries: where economic growth is found to have significant increasing effect on income inequality in short run while in the long run its’ effect is significant and decreasing. Population growth is the other variable which is found to have increasing effect on income inequality. Differently, FDI and low perception of corruption decrease income inequality. Therefore, much focus will have to be given to achieve sustainable development objective, promoting FDI and controlling of corruption. Also managing the population growth is important.